‘Terroristic Narratives: On the (Re)Invention of Peace in Northern Ireland’ - Cillian McGrattan (Terrorism and Political Violence, 2011)
It has been argued that a key factor in explaining the relative success of the Northern Ireland peace process is the role played by Non-Governmental Organisations (NGOs) and Community-Based Organisations (CBOs) in fostering dialogue and promoting shared space for cooperation across the communal divide. This article critically interrogates the normative import of that narrative, which implies that NGOs and CBOs occupy a higher moral ground than state-sponsored agencies. In large part this is attributed to both their indigenous character and their close proximity to terrorist violence. Indeed, several of these NGOs and CBOs are staffed by individuals who were convicted and imprisoned for terrorist-related offences. This article is less concerned with the actions of these non-state actors than with the political and moral foundations of the “peace consultancy industry,” which has grown up around the design, implementation, and ongoing evaluation of these projects. We argue that by importing tautological—and sometimes cynical—understandings of the term “peace,” these consultants risk complicity in reproducing the terroristic narratives that inspired and perpetuated the conflict in the first instance